Endoscopic ultrasound‐guided tissue acquisition of solid mass lesions of the pancreas: A retrospective comparison study of fine‐needle aspiration and fine‐needle biopsy. Issue 4 (5th January 2020) - Sweeney, Jacob; Soong, Lauren; Goyal, Abha
Abstract: Background: Although endoscopic ultrasound guided fine‐needle biopsy (EUS‐FNB) has emerged as an alternative to fine‐needle aspiration (FNA) for the sampling of solid pancreatic mass lesions, it remains unclear which method is more effective. We compared the diagnostic yields of FNA, FNB, and combined FNA/FNB at a tertiary care institution. Methods: Specimens from EUS‐FNA (04/2014‐08/2017) and EUS‐FNB (10/2015‐08/2017) with SharkCore needle of pancreatic solid mass lesions were retrieved. Clinical, radiologic, and pathologic data was recorded. Pathology results of malignancy/neoplasms with uncertain malignant potential were considered as true positive. The "negative" cases included were with ≥6 months of follow‐up. Nondiagnostic cases showed unremarkable pancreatic tissue, nonpancreatic elements, atypia, or features suspicious for malignancy. Diagnostic yield was defined as percentage of lesions sampled in which a benign or malignant tissue diagnosis, as defined above, was obtained. Statistical comparisons were performed using Fisher's exact test and univariable and multivariable logistic regression analysis. Results: The study cohort included 76 FNA only cases, 88 FNB only cases, and 40 combined FNA/FNB cases. Diagnostic yields were 70% (FNA), 70% (FNB), and 83% (FNA/FNB), which were not statistically different. Increase in lesion size and presence of ROSE were significantly associated with a diagnostic outcome on both univariable and multivariable analysis, unlike the number of passes. Conclusion: Our results demonstrate that for solid pancreatic lesions, the diagnostic yields of FNA, FNB, and combined FNA and FNB are comparable. Presence of ROSE and increasing lesion size increased the diagnostic yield while the number of passes had no significant impact.